On the rosenthal inequality for mixing fields - Fazekas, L.; Kukush, A. G.; Tómács, T. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
A proof of the Rosenthal inequality for α-mixing random fields is given. The statements and proofs are modifications of the corresponding results obtained by Doukhan and Utev.